PEMBANGUNAN EKONOMI DAN DISTRIBUSI PENDAPATAN ANTAR DAERAH DI DAERAH ISTIMEWA YOGYAKARTA - Udjianto, Didit Welly (Akutansi Bisnis & Manajemen ( ABM ), 2003)
The result of this research as follow from the three leading sektors analyzed corcerning with economy of Yogyakarta the period of 1975 - 1995 as shows that the value of structural change elasticity is defferent the tertiary sektor is the highest. The couses the allocation of development resources in the forms of facilities and infrastructure s needed to increase inputs among those sektors gives different influences. Structural change elasticity has altered the pattern of PDRB composition in Yogyakarta where previously an agricultural area, it is now dominated by service sektor. This condition couses the rise of the elements of growth inducement that is unequal and uneven. As the result, there is s tendency of more uneven societys income distribution in Yogyakarta, it means that the higher income per capita, the greater the rate of its unevenness.